Leadership as a Social Catalyst: Moderating the Relationship Between Talent Management and Job Satisfaction in Strategic Industries - Febrira, Sabrina; Iskandarini, Iskandarini; Siahaan, Elisabet (Baileo: Jurnal Sosial Humaniora, 2025)
Increasing business competition demands that companies manage human resources strategically, particularly through effective talent management and leadership, to enhance employee job satisfaction. This study aims to examine the influence of talent management on job satisfaction with leadership as a moderating variable, and to assess the extent to which leadership strengthens this relationship within the context of a strategic industry. A quantitative approach was applied using Moderated Regression Analysis (MRA) processed with SPSS version 25. The sample comprised 232 employees of PT Pupuk Iskandar Muda who had participated in talent management programs, possessed more than three years of work experience, and had undergone training. Sampling techniques combined proportionate stratified random sampling and judgment sampling. The findings reveal that both talent management and leadership have a positive and significant impact on job satisfaction. Specifically, leadership significantly strengthens the positive influence of talent management on job satisfaction. The study offers a novel contribution by mapping leadership as a social catalyst that reinforces the talent–satisfaction linkage, particularly in strategic industries that require integrated HR management. The research contributes conceptually to the fields of social sciences and humanities, especially in strategic leadership and talent development. Practical implications highlight the need to invest not only in talent programs but also in leadership capacity building.